PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN PADA PEMBELAJARAN TEMATIK DENGAN METODE GLOBAL KELAS 1 SDN KAJEN 02 - Gagas Pamulyo Aji; Sugeng Riyanto (Universitas Ahmad Dahlan, 2019)
This study aims to determine the improvement of early reading skills in studentsin using global methods for grade 1 Kajen Negri Elementary School 02. Background This study is that there are still many students who cannot read. Another condition is that many teachers present learning by emphasizing material that only focuses on thematic books and does not yet utilize contextual approaches. This research was conducted using two cycles. Each cycle consists of two meetings. The study subjects numbered 23 students, including 13 male students and 10 female students. The object of this research is the application of initial reading skills in the thematic learning subtheme 1 (me and a new friend). Data collection techniques in the form of tests, observations, documentation and interviews. Data analysis uses qualitative and quantitative analysis. The results of this study indicate that the application of global methods can improve initial reading skills in students. Students who get the value of complete reading skills in pre-cycle as much as 48% (11 students). In the first cycle the average value of students who completed 67, with a percentage of completeness of 61% (14 students). In the second cycle the average value of students who completed was 76.3 with a percentage of completeness 78% (18 students). It can be concluded that the global method can improve initial reading skills, thus the researcher's suggestions for teachers should apply the global method in beginning reading skills.